Gradus ad Parnassum - Fux, Johann Joseph 1660-1741 (Vienna Van Ghelen, 1725)
A highly influential treatise, the Gradus was published at imperial expense, with the Latin original followed by translations into German, Italian, English and French in whole or in part between 1742 and 1773. "The long history of influence exerted by the Gradus as a manual of composition (and not merely as a primer of strict counterpoint) has been documented by Alfred Mann. ... It was used extensively by Haydn, Mozart and Beethoven for pedagogical purposes, and it was cited and adapted in formal composition treatises by Marpurg, Albrechtsberger, Cherubini, Bellerman, Haller, Schenker, Roth and Tittel (Der neue Gradus, 1959), among others. In brief, it is no exaggeration to state that Fux has played a decisive role in the formation of Western musical thought in so far as tonal practice and technique are concerned. Fux's Singfundament (c1705) is a vocal primer whose solmization exercises anticipate the studies in imitation in the Gradus itself. It, too, has had a place in the afterlife of Viennese composition.
Johann Joseph Fux (c.1660-1741) was an Austrian composer, music theorist and pedagogue of the late Baroque era. His most enduring work is not a musical composition but his treatise on counterpoint, Gradus ad Parnassum, which has become the single most influential book on the Palestrinian style of Renaissance polyphony.
Index in facsimile 14I28
Ex libris Robert Volkmann (manuscript)
Brown leather binding, marbled endpapers, red edges
Keywords: 18th Century (1701-1800); Method; Music theory; Counterpoint; Austria